Problemas ambientales y su efecto en la calidad de vida de la población de la ciudad de Mazan Loreto, 2023 - Garcia Brünner, Marycielo (2024)
The population of the Mazan-Loreto district shows constant concern about the presence of contaminants in the local environment, reflecting as a serious and persistent problem that affects the community as a whole, a general concern stands out about direct consequences on the quality of life, since pollution directly impacts the health and well-being of residents. Lack of trust in government actions and pessimistic perception about solving problems indicate challenges in government effectiveness, the community of Mazan-Loreto faces significant environmental challenges, but also shows potential for collaboration and participation. The coherent perception of the severity of pollution highlights the need for comprehensive strategies that involve the community in environmental decision-making. The importance of improving environmental health management, addressing a lack of trust in government actions, and encouraging more active and trusted community participation is highlighted. The diversity of experiences and perceptions emphasizes the importance of adaptive approaches and specific strategies to improve quality of life and address environmental challenges effectively.